2007
DOI: 10.1134/s1063782607040070
|View full text |Cite
|
Sign up to set email alerts
|

EBIC characterization of strained Si/SiGe heterostructures

Abstract: Strained-Si/SiGe heterostructure is studied by the EBIC. The effect of annealing at 800• C is investigated. The EBIC images obtained at different beam energies are analyzed. The analysis of images obtained shows that misfit dislocation bunches in the graded SiGe layer could not explain the cross-hatch contrast dependence on Eb. Therefore, at least a part of this contrast should be associated with other defects located closer to the depletion region. It is assumed that dislocation trails could play a role of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Electrical active defects, named as dislocation trails, had been observed by EBIC in similar SiGe/Si heter-structures, which can also be annealed out at 800 0 C [6]. We suggest that the H1~H3 traps observed by DLTS in our as-grown SiGe/Si sample and the dislocation trail defects observed by EBIC in [6] might be due to the same grown-in defects, say agglomerates of vacancies generated by jog dragging. The generation of donor levels at 600 0 C might be related to the breakup of large vacancy clusters into smaller ones, which all dissolve at annealing temperatures over 800 0 C.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Electrical active defects, named as dislocation trails, had been observed by EBIC in similar SiGe/Si heter-structures, which can also be annealed out at 800 0 C [6]. We suggest that the H1~H3 traps observed by DLTS in our as-grown SiGe/Si sample and the dislocation trail defects observed by EBIC in [6] might be due to the same grown-in defects, say agglomerates of vacancies generated by jog dragging. The generation of donor levels at 600 0 C might be related to the breakup of large vacancy clusters into smaller ones, which all dissolve at annealing temperatures over 800 0 C.…”
Section: Discussionsupporting
confidence: 63%
“…Jog dragging can generate vacancies [4,5]. Electrical active defects, named as dislocation trails, had been observed by EBIC in similar SiGe/Si heter-structures, which can also be annealed out at 800 0 C [6]. We suggest that the H1~H3 traps observed by DLTS in our as-grown SiGe/Si sample and the dislocation trail defects observed by EBIC in [6] might be due to the same grown-in defects, say agglomerates of vacancies generated by jog dragging.…”
Section: Discussionmentioning
confidence: 99%
“…These defects usually deteriorate the photoelectric properties of CZT crystals by introducing different defect levels in the band gap, limiting the applications of the crystal. 6,7 The recombination activity of the carriers via dislocations is also found to be related to segregated or precipitated atoms of metallic impurities around dislocations. It was found that the electrical properties of the dislocations could either arise from intrinsic structural disorder, such as kinks or jogs, at dislocation cores 4,5 or from the debris of point defects (socalled dislocation trails) left behind by a dislocation glide.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the electrical properties of the dislocations could either arise from intrinsic structural disorder, such as kinks or jogs, at dislocation cores 4,5 or from the debris of point defects (socalled dislocation trails) left behind by a dislocation glide. 6,7 The recombination activity of the carriers via dislocations is also found to be related to segregated or precipitated atoms of metallic impurities around dislocations. 8 As for GaN, dislo-cations are considered to be acceptor-like, which can act as capture centers for electrons 9 and diffusion channels for both electrons and holes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, about 50% of photovoltaic solar cells are made of polycrystalline silicon, and dislocations are one of the major efficiency limitation defects. 8,9 Generally, the persistent presence of unintentionally introduced impurities and dislocation trail defects seriously interferes with interpreting experimental characterization results. The electrical activity of a dislocation can arise from intrinsic structural disorder ͑such as kinks or jogs͒ at dislocation cores, 2,3 shallow defect bands due to long-range strain fields, 4,5 extrinsic impurity/ precipitate decoration, 6,7 and the debris of point defects ͑socalled dislocation trails͒ left on dislocation glide planes.…”
Section: Introductionmentioning
confidence: 99%